IMPROVING STUDENT'S WRITING SKILL OF DESCRIPTIVE TEXT USING OUTDOOR ACTIVITY AT THE SECOND YEAR OF SMP NEGERI 1 KISMANTOROIN 2010/ 2011 ACADEMIC YEAR - Anjarsari, Dania Arip (2011)
The study aims at describing the implementation, result, and students' responses to the implementation of teaching English writing of descriptive text using Outdoor Activity. This classroom action research requires four procedures: planning, implementing, observing, reflecting. The subject of the study is the students of second year of SMP Negeri 1 Kismantoro consisting of 39 students. The data are taken from event, informant, and document The methods of collecting data are observation, test, interview, document. In this research the writer conducts three cycle. The findings show that the mean score of students' pre-test is 64 and the mean score of students' post-test is 75. Whereas in this study showed that an increase in study writing skill of descriptive text by 11% as indicates by the average score. This indicates that there is an improvement in students' writing skill of descriptive text. The students' responses to the implementation of outdoor activity are positive. It is proven by their enjoyment and enthusiasm during the implementation of outdoor activity.